Outcome of Management of Impacted Foreign Body in Upper Aero-digestive Tract (Bangladesh Journal of Otorhinolaryngology, 2024)
Background: Foreign body ingestion is a serious health problem in pediatric patients causing significant morbidity and mortality. A high index of suspicion and timely intervention can reduce morbidity as well as mortality especially in the pediatric age group. Time lag between the aspiration and expert attention is very important with regard to overall morbidity and mortality. Complications depend on its type, its localization and the duration of impaction. Large objects in the laryngotracheobronchial tree can cause obstruction to air passage leading to life threatening complications.Methods: This Prospective study was conducted at the department of ENT & head neck surgery, Dhaka Medical College Hospital for six months from December 2020 to May 2021. Patients attending in the study site with complaints of H/O ingestion of foreign body for inclusion of the study and final selection were done in according to the selection criteria inclusion was confirmed following signing written informed consent.Results: Hundred patients were seen at the study center during the period. All were emergencies patients with foreign bodies in upper aerodiagestive tract come to ENT & HNS dept.Majority of the patients of impacted esophageal foreign bodies represent pain, drooling of saliva. Females (38%) and males (62%), with a male to female ratio of 1.6:1. Sixty five (65%) patients had X-ray of the soft tissue neck (B/V), which was the main diagnostic tool. Ninety five (95%) patients were discharged after an uneventful postoperative recovery except post-operative pain, laceration of mucosa causes mild bleeding, erosion of nasal turbinate, vestibule, septal perforation & pyrexia from either the impacted foreign body or the procedure performed , which were managed by NG tube feeding , I/V antibiotic , medicated nasal pack conservatively. In this study, complication rate of 5% was recorded, about 50% of which was from impacted coin (in GIT). There were no cardiac arrest and death were recorded. Hospital stay ranged from a day to 7 days.Conclusion: FBs in the aero-digestive tract constitute a constant hazard in all age groups especially in children and elderly, which demands immediate action and management, delayed treatment with observation is not recommended. Bangladesh J Otorhinolaryngology 2023; 29(2): 96-103